The Role Of New Zealand Social Culture In Conflict Resolution - Avida Mileaningrum; Eri Radityawara Hidayat; Endro Legowo; Pujo Widodo; Achmed Sukendro (CV. AFDIFAL MAJU BERKAH, 2023)
New Zealand is a country with cultural diversity and multiculturalism principles. New Zealand's social culture also plays an important role in resolving conflict by creating spaces for open and inclusive dialogue. The principles of